Estimating urban air pollution from motor vehicle emissions using ALPR: A case study in Malang City, Indonesia - Sayono, Fajar Izzatunnimah; Semedi, Bambang; Setiawan, Raden Arief; Widyaningsih, Galih Edy Nur (Graduate School of Universitas Brawijaya, 2026)
Urban air quality is increasingly influenced by motor vehicle emissions, particularly in rapidly developing cities such as Malang, Indonesia. This study aims to quantify the contribution of motorized vehicles to urban air pollution by integrating Automatic License Plate Recognition (ALPR) technology with national emission factor standards. Traffic data were collected across several major urban road corridors in Malang City, representing both peak and non-peak traffic conditions. Detected vehicle types were subsequently reclassified in accordance with the Ministry of Environment Regulation No. 12 of 2010 to ensure consistency and accuracy in emission estimation. Emissions of key pollutants, including carbon monoxide (CO), nitrogen oxides (NO?), particulate matter (PM??), and sulfur dioxide (SO?), were estimated using a Tier 1 emission calculation approach. The results indicate that average daily CO emissions reached approximately 1,315 kg/day, with peak levels exceeding 1,450 kg/day during high-traffic weekdays. Similar trends were observed for other pollutants, reflecting strong correlations between traffic density and emission intensity. Motorcycles were identified as the largest contributors to total emissions across all measured pollutants, primarily because of their dominant share of daily traffic volume. These findings highlight the urgent need for targeted emission control policies that focus on high-frequency vehicle categories, especially two-wheelers. In addition, strategies such as improved traffic management, stricter emission standards, and enhanced fuel quality are essential to mitigate urban air pollution. Overall, this study provides empirical evidence to support more effective and sustainable urban air quality management policies in rapidly growing cities.